1979
DOI: 10.1177/030006057900700601
|View full text |Cite
|
Sign up to set email alerts
|

An Experimentally Controlled Evaluation of the Effect of Inositol Nicotinate upon the Digital Blood Flow in Patients with Raynaud's Phenomenon

Abstract: The vaso-active effects of inositol nicotinate (Hexopal) were investigated in thirty patients with primary and secondary Raynaud's phenomenon using several non-invasive experimental techniques under controlled conditions. The earlier formed impression that this drug requires a prolonged 'build-up' period was confirmed. Recording the time required to induce Raynaud's phenomenon as well as assessments of total and nutrient digital blood flow showed significant beneficial therapeutic effects upon the skin's micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…24 The small amount of data available that suggests IHN does not produce a flushing reaction is consistent with the modest NA plasma response following IHN intake. 23,24,40 Few other adverse effects have been reported in clinical trials studying the use of dosages of IHN up to 4,000 mg/ day. [40][41][42][43] There is debate about whether the bioavailability of NA from IHN is high enough to justify it being considered a form of niacin.…”
Section: Inositol Hexanicotinatementioning
confidence: 99%
See 1 more Smart Citation
“…24 The small amount of data available that suggests IHN does not produce a flushing reaction is consistent with the modest NA plasma response following IHN intake. 23,24,40 Few other adverse effects have been reported in clinical trials studying the use of dosages of IHN up to 4,000 mg/ day. [40][41][42][43] There is debate about whether the bioavailability of NA from IHN is high enough to justify it being considered a form of niacin.…”
Section: Inositol Hexanicotinatementioning
confidence: 99%
“…23,24,40 Few other adverse effects have been reported in clinical trials studying the use of dosages of IHN up to 4,000 mg/ day. [40][41][42][43] There is debate about whether the bioavailability of NA from IHN is high enough to justify it being considered a form of niacin. Some publications support this classification, 17 while others contradict it.…”
Section: Inositol Hexanicotinatementioning
confidence: 99%
“…The conclusions of these studies were as follows. In RP, symptomatic improvements were reported when IH was consumed for 3 (Holti 1979;Sunderland and others 1988) and 9 mo others 1977, 1981;Aylward 1979). Two studies (Aylward 1979;Holti 1979) assessed responses of flow, and increases were reported after 2, 3, and 9 mo of consumption (Aylward 1979;Holti 1979).…”
Section: R: Concise Reviews In Food Sciencementioning
confidence: 97%
“…. Table 1 outlines the 5 studies that investigated the effects of IH in RP, and 4 of them can be criticized because they are lacking a study control others 1977, 1981;Aylward 1979;Holti 1979;Sunderland and others 1988). The conclusions of these studies were as follows.…”
Section: R: Concise Reviews In Food Sciencementioning
confidence: 99%
See 1 more Smart Citation